Qaidah Furu’ Fi Al-Riba dan Implementasinya - Doli Witro; Mohamad Sar'an; Deden Effendi (IQTISHADUNA, 2021)
In the texts, namely the Al-Quran and hadith, many provisions are developed from the text itself, one of which is the rules of fiqh. There are many discussions of fiqh principles related to the muamalah contract and discussions outside the contract, such as usury. There are many verses of the Koran and hadiths that prohibit people from practicing usury so that usury is categorized as a grave sin and mujma’ ‘alaih. This paper briefly explains the rules of fiqh about usury. This study aims to understand the community of borrowing and borrowing or what kind of debt is categorized as usury. This article uses a qualitative approach that is the library in nature. The data in this study come from books and journals related to the topics discussed, namely the rules of furu’ fi al-riba. The data analysis technique used was data reduction, data presentation, and conclusion drawing. The results of the analysis show that muamalah transactions in any form are not prohibited, but muamalah transactions that are prohibited are muamalah transactions that contain elements of usury.